PERBANDINGAN PEMOHON DALAM PERKARA PEMBUBARAN PARTAI POLITIK ANTARA INDONESIA DENGAN SLOVENIA - Fhirman Sinaga; Emilda Firdaus; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The hallmark of the rule of law is a democratic system of government. In aconstitutional democratic system, the existence of political parties is a necessitybecause it will be a place to convey people's aspirations. The purpose of this studyis to find out how the legal arrangements for the dissolution of political parties inIndonesia and Slovenia. The research used is normative legal research which isusually only a document study.The data used are secondary data consisting of primary legal materials,secondary legal materials, and tertiary legal materials. The method used in thisresearch is the literature method, namely by conducting research from variousreading sources related to research. This data collection technique is carried outby reading, studying, reviewing and analyzing legal materials (primary andsecondary legal materials) by adjusting the problems studied by the author. Dataanalysis is by conducting an analysis with qualitative measures that rely onsubstance with data collection that concludes.The result of the study is the arrangement of the dissolution of politicalparties in Indonesia that the government has the right as an applicant in the caseof dissolution of a political party, while Slovenia that Everyone can apply.Keywords : Dissolution, Applicant, Government, Political Party.